Digital Transformation of Hizib Nahdlatul Wathan: Preserving Spiritual Heritage through Technology in the Living Qur’an - Ela Sartika; Izzatul Arab; Dewi Rapinta (UIN Kiai Haji Achmad Siddiq Jember, 2025)
This study investigates the digitization of the Hizib Nahdlatul Wathan recitation tradition among the Nahdlatul Wathan community in Lombok, Indonesia, within the framework of Living Qur’an studies. The Hizib Nahdlatul Wathan—a compilation of prayers, Qur’anic verses, and dhikr authored by TGKH Muhammad Zainuddin Abdul Madjid—serves as a vital spiritual practice, a symbol of religious identity, and an instrument of organizational solidarity. Amidst technological advancements and challenges such as geographical barriers and the COVID-19 pandemic, the tradition has transitioned to digital platforms, including mobile applications, e-books, flipbooks, and online audio recitations. Utilizing a qualitative descriptive methodology that involves observation, interviews, and documentation, the research demonstrates that digitization significantly enhances accessibility, temporal flexibility, and intergenerational continuity, particularly engaging younger, technology-oriented generations while maintaining spiritual intent and authenticity. Community responses are predominantly positive, praising the enhanced convenience and interactive features. However, concerns persist regarding the diminished solemnity, reduced communal interaction, and potential over-reliance on technology compared to traditional congregational readings. Framed by the Living Qur’an perspective, digitization emerges as a revitalizing force rather than a degrading one, enabling sacred texts to remain dynamic and contextually relevant in the digital era. Nonetheless, challenges persist in preserving profound spiritual depth and social bonds. The study concludes that thoughtful technological integration effectively safeguards Nahdlatul Wathan’s spiritual heritage, providing valuable insights for harmonizing religious traditions with modern innovations.